Challenges facing pregnant women in rural communities in Enugu State - Mercy Okeke, Nkechi; Ukamaka Nwachukwu, Ruphina; Ngozi F. , Nnaji (International Journal of Psychosocial Rehabilitation, 2024)
The study investigated the challenges facing pregnant women in rural communities in Enugu State. One research question was used to determine the challenges facing pregnant women in rural communities in Enugu State. A survey design was used. Data was collected using a questionnaire. A total of 108 pregnant women participated in the study. Data were analyzed using mean and standard deviation. The study revealed that lack of fund to attend antenatal, lack of information because of illiteracy, distance of antenatal care services, lack of transportation facilities to antenatal care services, delay in referral cases, physical violence during pregnancy and poor treatment from antenatal care service providers were crucial challenges facing pregnant women in the rural poor. Based on the study, the following recommendations are made: government should make empowerment education compulsory for women, the government should organize regular training for health workers to update their performance, community leaders should organize family counselling to husbands on the dangers of violence on the pregnant women and government should make antenatal and delivery services freely accessible for rural women to alleviate their economic burden